2022
DOI: 10.52804/ijaas2022.3217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land cover Dynamics on Ecosystem services value of Siwalik range of Madhesh Province Nepal

Abstract: The Siwalik region is the area that lies between the hills in the north and Terai in the south. It provides a wide range of services and is of particular interest from a land use land cover (LULC) change perspective as it is naturally fragile and prone to degradation. The study was conducted in Madhesh Province Siwalik to assess the LULC change over three time periods and to quantify the change in ecosystem services value (ESV) due to LULC change. Remote sensing, Google Earth Engine and Arc GIS were used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Between 2000 and 2019, the forest area of Nepal expanded by 1.7% on a national scale, while agricultural land diminished by 2.1% due to the expansion of built-up areas [55]. The Forest Survey of Nepal, conducted in 2019, reported that the district comprises a total forest area of 60,631 hectares, amounting to 55.9% of its total land area.…”
Section: Changes In Land Use and Land Covermentioning
confidence: 99%
“…Between 2000 and 2019, the forest area of Nepal expanded by 1.7% on a national scale, while agricultural land diminished by 2.1% due to the expansion of built-up areas [55]. The Forest Survey of Nepal, conducted in 2019, reported that the district comprises a total forest area of 60,631 hectares, amounting to 55.9% of its total land area.…”
Section: Changes In Land Use and Land Covermentioning
confidence: 99%